MODIFICATION TO THE BILGE AND SEA WATER PUMPS FITTED IN 17.5 METRE JINGHA TYPE TRAWLERS. - RANJAN, A (Fishery Technology, 2017)
This paper brings out the difficulties encountered with the Bilge and sea water circulating pumps which are fitted and drawn in series alongwith a fresh water pump in the 17.5 m. fishing trawlers.